2014
DOI: 10.3382/ps.2013-03812
|View full text |Cite
|
Sign up to set email alerts
|

Arginine affects appetite via nitric oxide in ducks

Abstract: The objective of the study was to investigate the mechanism by which arginine regulates feed intake in Pekin ducks. In experiment 1, one hundred forty-four 1-d-old male Pekin ducks were randomly allotted to 3 dietary treatments with 6 replicate pens of 8 birds per pen. Birds in each group were fed a corn-corn gluten meal diet containing 0.65, 0.95, and 1.45% arginine. Ducks fed the diet containing 0.65% arginine had lower feed intake and plasma nitric oxide level (P < 0.05) than the other 2 groups. In experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…Also, feed intake significantly increased by GAA dietary supplementation at 0.6 g/kg and upward levels. Appetite is sensitive to dietary arginine deficiency and thus impairs the growth and performance in meattype chickens (Kidd et al 2001;Labadan et al 2001;Attia et al, 2011) and ducks (Wang et al 2013(Wang et al , 2014. Also, by inhibiting the nitric oxide synthesis, the orexigenic effects of some peptide appetite regulators (such as neuropeptide Y and ghrelin) were attenuated (Gaskin et al 2003;Taksande et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, feed intake significantly increased by GAA dietary supplementation at 0.6 g/kg and upward levels. Appetite is sensitive to dietary arginine deficiency and thus impairs the growth and performance in meattype chickens (Kidd et al 2001;Labadan et al 2001;Attia et al, 2011) and ducks (Wang et al 2013(Wang et al , 2014. Also, by inhibiting the nitric oxide synthesis, the orexigenic effects of some peptide appetite regulators (such as neuropeptide Y and ghrelin) were attenuated (Gaskin et al 2003;Taksande et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, vitamin levels in SSD are lower compared to SAFE 105 diet (Table ). We came across some old publications, wherein it is shown that Arginine and Glycine have some role in promoting appetite and body weights in chicks and rats (Briggs, Luckey, Elvehjem, & Hart, ; Chyun & Griminger, ; Wang et al, ). But in our study, neither Arginine, Glycine nor the low vitamin level intakes can explain the low food intake and body weight, as the food intake and body weight values of hamsters fed low protein diet based on natural ingredients (NSD‐LPD) were almost comparable to those of hamsters fed control diet based on natural ingredients (NSD‐CD) (Table & Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors have further described that surplus dietary Arg elevates NO levels stimulating appetite and feed intake subsequently. On the contrary, insufficient dietary Arg lowers NO levels and alters hypothalamic protein expression inducing appetite inhibition further (Basoo et al, 2012;Wang et al, 2014aWang et al, , 2014b. Secondly, Arg possesses secretagogue activities that stimulate the release of growth and feed intake regulating pancreatic and pituitary hormones including glucagon, insulin, insulin-growth-factor-1 (IGF-1), somatotropin and neuropeptides among others (Barbul, 1986;Gaskin et al, 2003;Farr et al, 2005;Yang et al, 2007;Scanes, 2009).…”
Section: Discussionmentioning
confidence: 99%